Quadrupole-time-of-flight mass spectrometer modified for higher-energy dissociation reduces protein assemblies to peptide fragments. - Benesch, J; Ruotolo, B; Sobott, F; Wildgoose, J; Gilbert, A; Bateman, R; Robinson, C (2009)
The gas-phase dissociation of protein assemblies is becoming crucial for the application of mass spectrometry to structural biology. However certain aspects of the dissociation mechanism remain elusive. Moreover, many protein complexes resist dissociation at the energies accessible with current instrumentation. Here we report new insights into the collision-induced dissociation mechanism of protein assemblies. By holding activation energy constant and varying the charge state of the precursor ion, we show that the total charge of the precursor ion dramatically influences the internal energy required to dissociate monomers from the protein assembly. Furthermore, we have developed a modified quadrupole-time-of-flight instrument capable of accessing activation energies higher than previously possible. Under these conditions, protein assemblies eject subunits with excess internal energy that subsequently fragment into peptides. Together, these data indicate that the non-covalent dissociation is limited by the amount of charge available and not merely the activation energy, and they project the exciting possibility of extracting sequence information directly from intact protein complexes in the gas phase.